2015
DOI: 10.1021/acscatal.5b01521
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Selective Hydrogenation of α,β-Unsaturated Ketones to Unsaturated Alcohols on the Au25(SR)18 Cluster

Abstract: The Au 25 (SR) 18 cluster can catalyze 100% selective hydrogenation of α,β-unsaturated ketones to unsaturated alcohols. However, the mechanism remains a mystery. Here we unravel the underlying mechanism by using first-principles density functional theory calculations with benzalacetone as a substrate. We find that the Au 25 (SR) 18 cluster cannot directly activate either H 2 or benzalacetone separately. Instead, starting with coadsorption of H 2 and benzalacetone on Au 25 (SR) 18 , H 2 heterolytically cleaves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 49 publications
3
56
0
Order By: Relevance
“…Firstly,t he effect of the reactions olvents on the conversion of vanillin and the product selectivity was studied,b earing in mind the solvents' different properties such as polarity,b oilingp oint, and acid-base properties. [28] Although H 2 Oh as the strongest polarity,t he catalytic performance of Co/N-C-600 in the deoxygenation of vanillin in water was poorer than in the oxygen-containing organic solvents (Table 1, entries 7v s. 1-4). Generally,h igh conversions( 88.6-98.8 %) were achievedi no xygen-containing organic solvents (Table 1, entries 1-4), whereas conversionsw ere much lower in weak polar solvents without oxygen atoms (Table1,e ntries 5a nd 6).…”
Section: Catalytic Hydrodeoxygenation Of Vanillin In Various Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly,t he effect of the reactions olvents on the conversion of vanillin and the product selectivity was studied,b earing in mind the solvents' different properties such as polarity,b oilingp oint, and acid-base properties. [28] Although H 2 Oh as the strongest polarity,t he catalytic performance of Co/N-C-600 in the deoxygenation of vanillin in water was poorer than in the oxygen-containing organic solvents (Table 1, entries 7v s. 1-4). Generally,h igh conversions( 88.6-98.8 %) were achievedi no xygen-containing organic solvents (Table 1, entries 1-4), whereas conversionsw ere much lower in weak polar solvents without oxygen atoms (Table1,e ntries 5a nd 6).…”
Section: Catalytic Hydrodeoxygenation Of Vanillin In Various Solventsmentioning
confidence: 99%
“…The good dispersion of the Co/N-C-600 catalyst in the reactions olvent resultedi ni mprovingt he exposure of the catalyst to the substrate (vanillin) and the intermediate (vanillyl alcohol), thereby increasing the catalytic performance significantly.Inaddition, the oxygen-containings olvents might also have the ability to stabilizet he vanillyl alcohol intermediate through hydrogen bonding, which was believed to be favorable for reduction on the catalytic surface. [28] Although H 2 Oh as the strongest polarity,t he catalytic performance of Co/N-C-600 in the deoxygenation of vanillin in water was poorer than in the oxygen-containing organic solvents ( Table 1, entries 7v s. 1-4). One of the main reasons shouldb et hat the substrates (vanillin and vanillyl alcohol) were not sufficiently soluble in water,r endering ineffective the contact of the catalyst with the substrates.…”
Section: Catalytic Hydrodeoxygenation Of Vanillin In Various Solventsmentioning
confidence: 99%
“…Density functional theory (DFT) calculations revealed a mechanism based on the heterolytic cleavage of H 2 via FLPs at the SPO-gold interface. 11 Ouyang and Jiang 27 have also discussed the possibility of a heterolytic dissociation of H 2 at the goldbenzalacetone interface. The Au δ+ ---H δ--H δ+ ---O δ-=C δ+ -R would explain the preferential hydrogenation of C=O over C=C with gold catalyst.…”
Section: Gold Catalysis For Selective Hydrogenation Of Aldehydes and mentioning
confidence: 99%
“…This point has been confirmed by their DFT calculations. Ouyang and Jiang [37] found that Au 25 (SR) 18 shows 100% selectivity towards unsaturated alcohols for the hydrogenation of ␣,␤-unsaturated ketones. DFT calculations indicated that the preferential hydrogenation on C O bonds over C C bond might be benefited from the H bond interaction and solvent effect (Fig.…”
Section: Organic Modification Controls the Chemoselectivitymentioning
confidence: 99%
“…However, high activity catalysts usually lead to poor selectivity such that these metals could not be employed alone in most cases. To achieve high selectivity, the active centers should be dilute through alloying or isolated by inorganic species (such as CO, H and S) [24][25][26][27][28][29][30] and/or organic compounds (such as amines and thiol) [22,[31][32][33][34][35][36][37]. The most famous catalyst developed for this purpose is Lindlar catalyst (Pd-Pb/CaCO 3 ), which is commercially used for the selective hydrogenation of alkynes to alkenes [38,39].…”
Section: Introductionmentioning
confidence: 99%